Pelaksanaan Rekrutmen Tenaga Pendidik dan Kependidikan di Sekolah Dasar Islam Terpadu Lan Tabur Kota Pagar Alam - Pasiska, Pasiska; Mutyati, Mutyati; Kanada, Rabial (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
This study aims to see the implementation of recruitment at SDIT Lan Tabur, Pagar Alam city. Recruitment is the process of getting a number of qualified human resources to occupy a position or job. The implementation of professional and proportional recruitment will result in input of quality educators. To study the implementation of recruitment at SDIT Lan Tabur Kota Pagar Alam, using descriptive qualitative research that produces descriptive data in the form of written, spoken words and the activities of the people being observed. To collect data using interview techniques, observation techniques, and documentation techniques. The data analysis procedure used in this research is qualitative analysis. The results of the research obtained the following results: Implementation of the recruitment carried out was quite good, here it appears that there are various processes carried out by the school such as through administrative filing and tests for prospective new workers, most of the expected goals are achieved even though there are still inhibiting factors such as the difficulty of getting a workforce that is in accordance with the academic field with the field required by the school. However, in this case, the school, especially the principal and other workers, are equally trying to make the school a school that is in demand by the community.